An evaluation of the acceptance of drone technology services for control of fall armyworm in Northern Ghana - Asante, Isaac Kwasi (University of Cape Coast, 2021)
Modern technologies have demonstrated the potential to significantly boost agricultural production. The use of drones in agriculture has been popular inrecent years because it enhances existing rudimentary tools and practices in agricultural fields. The use of drone for control of the Fall Armyworm (FAW), which has drawn international attention due to its highly destructive nature in destroying many major crops, especially maize, is not popular. To this end, the Technical Centre for Agriculture (CTA) supported a collabourative research project to examine the efficacy of a synthetic chemical for FAW control using drone in three selected districts in Northern Ghana. After the project little is, however, known about how farmers are willing to accept drone technology for control of FAW. This study sought to examine the acceptance of drone technology services for control of FAW among maize farmers in the selected districts in Northern Ghana. Adopting the mixed methods approach to collect quantitative and qualitative primary data from150 maize farmers in the study area, measures of central tendencies, chi-squre, paired sample t-test, OLS regression and PLS-SEM were utilized to analyzed the quantitative data whilst thematic analysis was used to analyze the qualitative data. The results showed that, perceived usefulness, ease of use, attitude towards use and subjective norm accounted for 67% of farmers’ intention to adopt the technology for control of FAW. The Ministry of Food and Agriculture and its stakeholders should work on improving the attitude of farmers towards the utilization of drone technology for control of FAW through field demonstrations where the usefulness and ease of use of the technology can be observed by the farmers and their significant associates who influence the intention of the farmers to adopt the technology.
xviii,363p:,ill
Keywords: Acceptance; Fall Armyworms; Drone Technology; Maize Farmers; Northern Ghana; Extended Technology Acceptance Model (TAM3)